Design and Simulation of Methanol Production Process from CO2 and CO Hydrogenation with Reverse Water-Gas Shift Reaction - Ban, Sagar; Shrestha, Rakesh; Devkota, Sijan (Kathmandu University Journal of Science, Engineering and Technology, 2020)
Over the past century, Due to the excessive utilization of fossil fuels and increasing population around the globe, the anthropogenic emissions of CO2 have increased drastically. The captured CO2 can be utilized as to turn into a profitable business in addition to its positive impact of controlling the CO2 concentration in the atmosphere. A production process of high purity methanol from CO2 captured has been discussed in detail in this paper. The process is designed and simulated with Pro/II V.10.2. A comparison is made of the overall methanol yield resulting from consideration of only CO2 hydrogenation and the reverse water gas shift reaction with the addition of CO hydrogenation reaction in the reactor. The reaction set was chosen accordingly. The balance on CO2 in the process showed that it is possible to abate 2.12 tonnes of CO2 per tonne of methanol produced. The CO2 and H2 were used in the ratio 1:3 and the methanol so obtained was 4139 kg/h (overall yield of 0.47) with 99 % purity. This shows that the reaction kinetics and the process flow proposed in this paper can be employed.